(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Globally, cancer is a leading cause of death, with cervical cancer being particularly prevalent in sub-Saharan Africa, including Kenya. Despite being preventable, cervical cancer remains a significant health burden due to low screening awareness and socioeconomic disparities. In Kenya, it is the second most frequent cancer among women. This is exacerbated by high HPV infection rates, underscoring the critical need for effective screening strategies. This study assessed the knowledge, attitudes, and prevalence of cervical cancer screening among women in Garissa County. Methods: A descriptive cross-sectional study involving 480 women was conducted in Savannah Royal Hospital, Garissa from January 31st to February 4th, 2023. The study employed questionnaires to assess the knowledge and attitudes of women toward cervical cancer screening, alongside visual inspection with acetic acid (VIA) to determine the prevalence of cervical cancer. Participants were selected through convenience sampling after a public awareness drive, and informed consent was obtained from all participants. Results: Of 480 women screened, 96% (462) and 4% (18) tested negative and positive for cervical cancer, respectively. Notably, 66% (315) were unaware of cervical cancer screening prior to the study, with 82.1% citing lack of awareness as the reason for not being previously screened. Regarding attitudes, 65.1% reported no discomfort during screening, 71.9% rated the experience positively, and 50% felt no embarrassment in seeking a repeat VIA or Papanicolaou smear. Most women (72%) preferred receiving the results in person, and 97% were willing to undergo follow-up tests if the screening results were positive. Conclusion: The study highlights a significant lack of awareness of cervical cancer screening among women in Garissa County, yet reveals positive attitudes toward screening. This suggests that enhancing awareness could lead to higher screening participation. The 4% positivity rate emphasizes the necessity of ongoing screening initiatives.